Effect of menu labeling on the food choices of selected employees of a company. - Juanico, C. B.; Hurtada, W. A.; Food labeling (2003)
This study was undertaken to determine the effect of menu labelling on the food choices of selected employees of a company. Results showed that menu labels affected the food choices of the respondents. Ninety-four percent preferred to see the labels, while 63% used the labels to select their meals. Seventy-eight percent (78%) of those who used the menu labels ordered lower calorie dishes. The frequency of consumption of low calorie dishes like vegetables and fish increased. Socio-demographic, nutrition and health characteristics did not significantly affect food choices of the respondents. The likelihood to use the menu labels was higher among young adults, among male respondents, those who had college education, respondents with gross monthly income above Php 20;000, those who were either overweight or obese or even those who were healthy and had no family history of disease.
Keywords: Food labeling; Food consumption